2013
DOI: 10.1039/c3cp51668g
|View full text |Cite
|
Sign up to set email alerts
|

A computational study of the protonation of simple amines in water clusters

Abstract: The microsolvation study of a group of amines with a variable number of water molecules was performed by conducting a theoretical analysis of the properties of the clusters formed by the amines with up to seven molecules of water. We describe the microsolvation of several amines focusing on the dissociation of a water molecule that transfers a proton to the amine and forms a hydroxide ion. Ab initio calculations were performed on these clusters employing the DFT/B3LYP and MP2 methods with the 6-311++G(2d,p) ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…But, as per an MD simulation, the amine group can form 1.77 hydrogen bonds with water molecules, while the reference interaction site model(RISM) predicted 2.4 hydrogen bonds per the same moiety. Marta et al . studied the structures of the hydrated clusters of methylamine by applying density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…But, as per an MD simulation, the amine group can form 1.77 hydrogen bonds with water molecules, while the reference interaction site model(RISM) predicted 2.4 hydrogen bonds per the same moiety. Marta et al . studied the structures of the hydrated clusters of methylamine by applying density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…It is known, however, that implicit continuum solvation models do not satisfactorily treat specific solvent-solute interactions, which are important for accurate description of the solvation of amines in protic solvents. 16 Indeed, when one or two explicit water (or MeOH) molecules were included to account for hydrogen bonding with solvent, the lowest-energy conformers of 8 and 9 (Scheme 2a, b), would now lead to the experimentally observed diastereomers 5a and 6a upon protonation from the exo faces. This computational model predicts diastereomeric ratios that are in good agreement with the experimental values.…”
Section: Scheme 1 Synthetic Approaches To N-aryl Piperidinesmentioning
confidence: 99%
“…13 C NMR (151 MHz, CD3CN) δ 175 16,. 137.28, 127.97, 118.26, 114.02, 59.16, 54.43, 46.19, 42.73, 35.23, 32.18, 27.77, 26.43, 23.21, 23.20, 21.63, 19.85.…”
mentioning
confidence: 99%
“…They concluded that both forms, HL p and HL s , are formed in the first protonation step but HL p is predominant with a %-fraction of 86%. Clearly, even in some cases, where the same experimental technique was used, such as 13 C NMR, polyamines [25,26]. General shortcomings as well as advantages of each levels of theory tested here are well-known.…”
Section: Introductionmentioning
confidence: 95%